The China effect on regional economic integration: a longitudinal study of Central, South, and Southeast Asia - Liu, Hong (2024)
Does China’s growing economic presence pose an opportunity or a threat to regional economic integration? The authors answer this question by analyzing longitudinal and cross-country evidence from three regions, Central, South, and Southeast Asia. A unique panel dataset detailing bilateral economic cooperation and each economy’s political-economic factors from 2000 to 2019 was examined. This study concludes that (1) inbound foreign direct investment from China is positively associated with a country’s intra-regional integration, (2) trade ties to China show a negative relationship with intra-regional integration, and (3) the level of a country’s regional economic integration is conditioned by domestic economic and political factors such as transportation and information connectivity, per capita GDP, population size, trade openness, and public governance. This article contributes to the literature by using fresh cross-regional evidence to decipher the China effect on regional integration, embedding the political economy at both national and regional levels, and identifying variations and significance of various political-economic factors.